Proton-detected solid-state NMR detects the inter-nucleotide correlations and architecture of dimeric RNA in microcrystals. Issue 96 (3rd November 2017) - Yang, Yufei; Xiang, ShengQi; Liu, Xiaodan; Pei, Xiaojing; Wu, Pengzhi; Gong, Qingguo; Li, Na; Baldus, Marc; Wang, Shenlin
Abstract : A novel proton-detected solid-state NMR experiment detects the NH⋯N H-bonds within the Watson–Crick base pairs of RNA in crystals. Abstract : We report a novel proton-detected MAS solid-state NMR strategy based on 15 N– 15 N proton assisted recoupling to detect the inter-nucleotide NH⋯N hydrogen bonds within the Watson–Crick base pairs of micro-crystallized dimeric RNA and to confirm the kissing-loop structure. This would contribute to advances in the structural determination of RNA using solid-state NMR.